DAUGHTERS OF THE DIVINE: EXPLORING THE HIDDEN LIVES OF KASHMIRI SUFI WOMEN - FAHEEM AHMAD DAR , DR. G RANGARAJAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Sufism, the mystical aspect of Islam grounded on the Quran and the life of the Prophet Muhammad (PBUH), represents the pursuit of divine love, self-purification, and ultimate communion with God. Although early Islamic mysticism has mostly been chronicled via male saints, the impact of female mystics is as significant, influencing spiritual traditions throughout the ages. Figures like Rabia al-Adawiyya, Fatima of Nishapur, and Jahanara Begum defined avenues of divine devotion that surpassed gender constraints, providing models of piety, wisdom, and asceticism. In the setting of Kashmir, female mystics significantly influenced the spiritual landscape of the Valley. Kashmiri women, shown by Lal Ded's global monism and the mystical experiences of Sham Ded, Shanga Bibi, Bahat Ded, Taj Khatun, and Bibi Baria, epitomized perseverance, compassion, and spiritual authority, often maintained via oral traditions and local shrines. Their shrines and teachings exemplify the gender-inclusive principles of Kashmiri Sufism, whereby women engaged as searchers, mentors, and guardians of spiritual knowledge. Restoring their narratives enhances the comprehension of Sufi traditions as a collective journey for both men and women, while underscoring the profound foundations of egalitarian spirituality within Kashmir’s cultural and religious legacy. This study underscores the significant influence of women mystics on the development of Islamic spirituality, spanning from Rabia al-Adawiyya to Kashmiri saints such as Lal Ded and Sham Ded. It emphasizes how their commitment and doctrines enhanced Sufism, validating its inclusive and egalitarian nature.